Cloning and orientation of the gene encoding polynucleotide phosphorylase in Escherichia coli. - Crofton, S (1983)
Mutations which affect the activity of polynucleotide phosphorylase (PNPase) map near 69 min on the bacterial chromosome. This region of the chromosome has been cloned by inserting the kanamycin-resistant transposon Tn5 near the argG and mtr loci at 68.5 min. Large SalI fragments of chromosomal DNA containing the Tn5 element were inserted into pBR322, and selection was made for kanamycin-resistant recombinant plasmids. Two of these plasmids were found to produce high levels of PNPase activity in both wild-type and host strains lacking PNPase activity. The pnp gene was further localized and subcloned on a 4.8 kilobase HindIII-EcoRI fragment. This fragment was shown to encode an 84,000-molecular weight protein which comigrated with purified PNPase during sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The orientation of the pnp gene was determined by insertion of Tn5 into the 4.8 kilobase fragment cloned in pBR322. Some of the insertions had lost the ability to elevate the level of PNPase activity in the host bacterium. Restriction mapping of the positions of the Tn5 insertions and analysis of plasmid-encoded polypeptides in UV-irradiated maxi-cells indicated that the pnp gene is oriented in the counterclockwise direction on the bacterial chromosome.